(untitled) (Global Journal of Medical Research, 2020)
Bronchial asthma is a multifactorial disease. Industrial chemical compounds are also included in the list of causative factors of bronchial asthma. The contribution of industrial allergens to the formation of bronchial asthma is undeniable. In studies carried out in conjunction with professional pathologists, children were found to be sensitized to industrial allergens (nickel, chromium, formaldehyde, etc.), which contribute to the formation of bronchial asthma. However, determining factor, is the presence of atopy.